2013
DOI: 10.1029/2012ja018146
|View full text |Cite
|
Sign up to set email alerts
|

Ion gyroharmonic structures in stimulated radiation during second electron gyroharmonic heating: 1. Theory

Abstract: [1] Stimulated electromagnetic emissions (SEEs) may provide important diagnostic information about space plasma composition, energetics, and dynamics during active experiments in which ground-based high-powered radio waves are transmitted into the ionosphere. The nonlinear plasma processes producing this secondary radiation are not well understood particularly for some recent observations where the transmitter (pump) frequency is near the second harmonic of the electron gyrofrequency. New, more comprehensive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(73 citation statements)
references
References 42 publications
6
67
0
Order By: Relevance
“…[15] Discrete narrowband spectral features within 1 kHz of the pump frequency separated by multiples of the ion gyro-frequency f ci observed in the SEE spectrum have been attributed to the simultaneous parametric decay of upper hybrid/electron Bernstein waves into multiple upper hybrid/electron Bernstein and ion Bernstein waves , Samimi et al, 2012a, 2012b. As stated in section 1, this process will be referred to here as Stimulated Ion Bernstein SIB Scatter (SIBS) .…”
Section: Discrete Ion Gyro-features For F 0 3f Cementioning
confidence: 99%
See 3 more Smart Citations
“…[15] Discrete narrowband spectral features within 1 kHz of the pump frequency separated by multiples of the ion gyro-frequency f ci observed in the SEE spectrum have been attributed to the simultaneous parametric decay of upper hybrid/electron Bernstein waves into multiple upper hybrid/electron Bernstein and ion Bernstein waves , Samimi et al, 2012a, 2012b. As stated in section 1, this process will be referred to here as Stimulated Ion Bernstein SIB Scatter (SIBS) .…”
Section: Discrete Ion Gyro-features For F 0 3f Cementioning
confidence: 99%
“…Recent studies at the High Frequency Active Auroral Research Program (HAARP) facility, showed new SEE spectral features within 1 kHz of the pump frequency due to so-called Stimulated Ion Bernstein Scatter (SIBS) during pump heating near the second electron gyro-harmonic 2f ce Scales et al, 2011;Samimi et al, 2012aSamimi et al, , 2012b. SEE spectral structures ordered by harmonics of the ion gyro-frequency f ci (near 50 Hz) were observed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scattering by ion-cyclotron waves (e.g. Shukla and Tagare 1979;Samimi A. et al 2013) and drift waves (Shukla et al 1984) can then be important. Related experiments have later been outlined for piezoelectric semiconductor plasmas (e.g.…”
Section: Introductionmentioning
confidence: 99%